p70S6K/Akt dual inhibitor DIACC3010 is efficacious in preclinical models of gastric cancer alone and in combination with trastuzumab - Shota Fukuoka; Yoshikatsu Koga; Mayumi Yamauchi; Shigehiro Koganemaru; Masahiro Yasunaga; Kohei Shitara; Toshihiko Doi; Takayuki Yoshino; Toshio Kuronita; Brian Elenbaas; Pamela Wahra; Hong Zhang; et al. (Scientific Reports, 2023)
Abstract The PI3K-Akt-mTOR (PAM) pathway is implicated in tumor progression in many tumor types, including metastatic gastric cancer (GC). The initial promise of PAM inhibitors has been unrealized in the clinic, presumably due, in part, to the up-regulation of Akt signaling that occurs when the pathway is inhibited. Here we present that DIACC3010 (formerly M2698), an inhibitor of two nodes in the PAM pathway, p70S6K and Akt 1/3, blocks the pathway in in vitro and in vivo preclinical models of GC while providing a mechanism that inhibits signaling from subsequent Akt up-regulation. Utilizing GC cell lines and xenograft models, we identified potential markers of DIACC3010-sensitivity in Her2-negative tumors, i.e., PIK3CA mutations, low basal pERK, and a group of differentially expressed genes (DEGs). The combination of DIACC3010 and trastuzumab was evaluated in Her2-positive cell lines and models. Potential biomarkers for the synergistic efficacy of the combination of DIACC3010 + trastuzumab also included DEGs as well as a lack of up-regulation of pERK. Of 27 GC patient-derived xenograft (PDX) models tested in BALB/c nu/nu mice, 59% were sensitive to DIACC3010 + trastuzumab. Of the 21 HER2-negative PDX models, DIACC3010 significantly inhibited the growth of 38%. Altogether, these results provide a path forward to validate the potential biomarkers of DIACC3010 sensitivity in GC and support clinical evaluation of DIACC3010 monotherapy and combination with trastuzumab in patients with HER2- negative and positive advanced GCs, respectively.